2008
DOI: 10.1161/hypertensionaha.107.101444
|View full text |Cite
|
Sign up to set email alerts
|

Prorenin and Renin-Induced Extracellular Signal-Regulated Kinase 1/2 Activation in Monocytes Is Not Blocked by Aliskiren or the Handle-Region Peptide

Abstract: Abstract-The recently cloned (pro)renin receptor [(P)RR] mediates renin-stimulated cellular effects by activating mitogen-activated protein kinases and promotes nonproteolytic prorenin activation. In vivo, (P)RR is said to be blocked with a peptide consisting of 10 amino acids from the prorenin prosegment called the "handle-region" peptide (HRP). We tested whether human prorenin and renin induce extracellular signal-regulated kinase (ERK) 1/2 activation and whether the direct renin inhibitor aliskiren or the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
220
1
3

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(230 citation statements)
references
References 36 publications
6
220
1
3
Order By: Relevance
“…Aliskiren does not inhibit binding of (pro)renin to the (P)RR, 87,118 nor does it prevent (pro)renin-induced cell signaling. 87,118,120 However, in STZ-diabetic mRen-2 rats treated with aliskiren for 10 weeks, in situ hybridization on renal sections revealed a clear reduction in gene expression of the (P)RR in the glomeruli and tubular cells compared with vehicle-control diabetic mRen-2 rats. 87 Interestingly, in vitro studies showed that aliskiren did not affect gene expression of (P)RR in mesangial cells.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 97%
See 2 more Smart Citations
“…Aliskiren does not inhibit binding of (pro)renin to the (P)RR, 87,118 nor does it prevent (pro)renin-induced cell signaling. 87,118,120 However, in STZ-diabetic mRen-2 rats treated with aliskiren for 10 weeks, in situ hybridization on renal sections revealed a clear reduction in gene expression of the (P)RR in the glomeruli and tubular cells compared with vehicle-control diabetic mRen-2 rats. 87 Interestingly, in vitro studies showed that aliskiren did not affect gene expression of (P)RR in mesangial cells.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 97%
“…However, attempts by other investigators to reproduce the cellular effects of the blocker, and its in vivo benefits (although in nondiabetic models of renal damage), have largely been unsuccessful. 115,118,131,132 Replication by others of the experimental designs used by Ichihara and coworkers may clarify some of the questions on the function of the (P)RR in DN and in tissue damage in general.…”
Section: Aliskiren Localizes In the Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…The handle region peptide (HRP), a putative blocker of the (P)RR, could efficiently block glomerulosclerosis, 86,88,95,96 while RAS inhibitors were unable to prevent end-stage organ damage associated with diabetes. 97,98 However, not all investigators were able to reproduce the inhibitory effects of HRP either in vivo or in vitro. 97,99 In diabetic subjects, prorenin to active renin ratio is very high.…”
Section: Implication Of (P)rrs In Pathologic Conditionsmentioning
confidence: 99%
“…97,98 However, not all investigators were able to reproduce the inhibitory effects of HRP either in vivo or in vitro. 97,99 In diabetic subjects, prorenin to active renin ratio is very high. This is supported from studies where the excessive non-proteolytic activation of (P)RR-bound prorenin has a major role in diabetic nephropathy and retinopathy, and cardiac fibrosis.…”
Section: Implication Of (P)rrs In Pathologic Conditionsmentioning
confidence: 99%